Selective Heat Input for Low Temperature Metallic Wafer Level Bonding. (8th September 2020) - Wiemer, Maik; Hofmann, Christian; Vogel, Klaus
Abstract : This paper focuses on two innovative bond technologies, which enable a selective heating of the bond interface only. The reactive bonding with the new CuO/Al multilayer system could by successfully used for wafer bonding. With a tool pressure of 0.5 to 5 bar an average shear strength of 64 N/mm² for Si-glass and 143 N/mm² for Si-Si could be reached. The bond time is < 1 s due reaction velocities of 28 m/s to 40 m/s. The focus of inductive bonding is the support and enhancement of the solid-liquid interdiffusion (SLID) process at wafer level by using selective and energy-efficient induction heating of Cu-Sn layers. With IR thermography, the heat distribution and the achieved heating rate of approx. ∆T = 150 K/s could be investigated. By applying a tool pressure of 2 MPa and a bond time of 120 s an average shear strength of 68 N/mm² could be achieved.